Species of Sea Urchins (Echinoidea) in the Intertidal Zone of Pahawang Island, Pesawaran, Lampung - Jeane Siswitasari Mulyana; Gres Maretta; Muhammad Aqil Maulana; Novriadi Novriadi; Andy Darmawan (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Sea urchins are susceptible to environmental changes, including ones caused by anthropogenic activities in coastal area. They are commonly found in coral reef areas, seagrass beds, and mixed sand and coral rubble substrates. These marine ecosystems face critical problem as a result of water pollution, thus affecting their ecological roles as habitats for sea urchins. Pahawang Island is located in the Lampung Bay area and has substrate characteristics that are suitable for the habitat preferences of sea urchins. On the contrary, Pahawang Island becomes famous tourist destination and this can potentially cause damage to habitats of sea urchin. The purpose of this research is to identify sea urchin species (Echinoidea) in the intertidal zone of Pahawang Island, Lampung. Methodology: Samples were collected using surveying method by walking along the intertidal zone during low tide. Sampling locations include Jelarangan Hamlet, Suwak Buah Hamlet, Andreas Resort around Kalangan Hamlet, and Pahawang Hamlet. Sea urchins were identified based on morphological characteristics. Findings: Sea urchins found in the intertidal zone of Pahawang Island consist of four species: Echinothrix calamaris, Diadema setosum, and Diadema antillarum, and Mespilia globulus. E. calamaris and D. setosum were found on substrates such as seagrass beds, coral, and sand, while Diadema antillarum and Mespilia globulus were only found in waters with coral substrates. These four species of sea urchins inhabit diverse habitats and play important ecological roles in the ecosystem, even influencing the conditions of other benthic organism communities in intertidal zone of Pahawang Island. Contribution: This study provides baseline data on sea urchin species within specific area to later plan conservation strategies related to human-induced environmental changes.